Teachers’ Values for the Profession in Agricultural Higher Education System (Indian Journal of Extension Education, 2017)
Values an individual holds play an important role in personal life as well as professional life. In this study an attempt was made for identifying the values held by agricultural teachers in the selected universities viz., ICAR- IARI, New Delhi; ICAR- NDRI, Karnal; TNAU, Coimbatore; and UAS, Bangalore. A standard Likert-type scale was developed for assessing the values held by teachers. Most of the teachers gave similar responses and they valued more strongly the ability to share experiences and knowledge with students.